Can History Be Open Source? Wikipedia and the Future of the Past. - Rosenzweig, Roy (Journal of American History, 2006)
The article presents information on Wikipedia, an online encyclopedia that contains articles about history. Wikipedia allows Internet users to freely read and use articles, thus, making it the most significant application of the principles of the free and open-source software movement to the world of cultural production. Astonishingly, Wikipedia has become widely read and cited, with more than a million people a day visiting the site. The article also offers information on other Web-based encyclopedias that were developed before Wikipedia.